Gamification in digital marketing for e-commerce: a ‎review of strategies to boost engagement and sales - Saber Rashid, Nazik; R. M. Zeebaree , Subhi (International Journal of Scientific World, 2025)
Gamification has become an innovative and strategic approach within digital marketing, ‎particularly for e-commerce platforms striving to enhance customer engagement, drive sales, and ‎cultivate brand loyalty. Despite its growing adoption, the academic understanding of its ‎mechanisms, implications, and sustainability remains underexplored. This comprehensive review ‎integrates empirical evidence and theoretical perspectives to construct a robust framework for ‎evaluating gamification strategies in e-commerce. The analysis identifies pivotal elements leaderboards, challenges, and incentive structures and their influence on consumer behavior ‎across diverse contexts. Four overarching themes emerge: enhanced consumer loyalty, increased ‎purchase frequency, strengthened brand engagement, and the critical importance of ethical design. ‎Furthermore, the study underscores challenges such as sustaining long-term user commitment and ‎addressing ethical dilemmas related to transparency and manipulation. By offering practical ‎guidelines for implementation and illuminating areas for further inquiry, this research contributes to ‎the scholarly discourse on gamification as a dynamic tool in digital marketing. It establishes a ‎foundation for advancing its application in an ethically responsible and consumer-centric manner‎.